Lived Experiences of Childfree Lesbians in the United Kingdom: A Qualitative Exploration. (December 2018) - Clarke, Victoria; Hayfield, Nikki; Ellis, Sonja J.; Terry, Gareth
Evidence suggests that most lesbians remain childless, but little is known about the childfree lesbian experience. The current study qualitatively explores the experiences of five childfree lesbians. The results show that even for a group for which childlessness is arguably still presumed, it remains socially difficult to articulate a desire to remain childfree. The women presented their childfreedom as both essential and politically and biographically motivated. Being lesbian and childfree was framed as different from being heterosexual and childfree—discourses and practices of "families of choice" and "co-independence" in intimate partnerships provided a way of "doing" family outside of dominant, heteronormative expectations. Concurrently, the greater visibility of lesbian parenting had resulted in the unwelcome imposition of heteronormative expectations. The results raise questions about the normalizing effects of the legal recognition of same-sex marriage and queer parenthood on the lives of lesbian women, and other queers, who choose to remain childfree.